Loneliness and Social Support as Characteristics of Social Health and Factors of Social Media Addiction among Adolescents - D.S. Kornienko; N.A. Rudnova; T.O. Gordeeva; O.A. Sychev; V.A. Egorov; A.N. Veraksa (Moscow State University of Psychology and Education, 2023)
Objective. The goal of the study was to look at how different levels of social health (loneliness and social support) show up in different ways in terms of how dependent people are on their social networks. Background. Loneliness and social support are considered as indicators of a teenager's social health, characterizing the inner experience of isolation from others and the breadth of the circle of contacts that a teenager can turn to for help. Previously, the question of their relationship in the context of their dependence on social networks was not considered. Study design. The current study examined the differences in social media addiction, motive, and formal characteristics of social media use among groups of adolescents with different levels of social health (loneliness and social support). Participants. The study sample was made up of 6405 13–18-year-olds ( M = 15, SD = 1,46), 42,2% of them male, who went to school in Yakutsk, which is in the Republic of Sakha (Yakutia). Measurements. The following methods were used: the three-point Loneliness Scale, the Social Support Scale, and the Bergen Social Network Addiction Scale. The motives for using social networks and the formal characteristics of their use were identified. Results. Teenagers were put into groups based on how lonely they were and how much social support they had. These groups show that dependence on social networks shows up in various ways. The groups with different levels of loneliness and social support can be identified by the reasons they use social networks and the way they work (how long they use them and how many friends they have). The use of social networks by adolescents with high levels of loneliness and low levels of social support leads to negative results and forms addiction due to the effects of compensation and diminution. Adolescents with low loneliness and high social support, on the other hand, demonstrate positive effects from the use of social networks. Conclusions. Among indicators of social health, low social support ...